2019
DOI: 10.3390/geosciences9100453
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Dynamics from Synoptic to Local Scale During an Intense Frontal Dust Storm over the Sistan Basin in Winter 2019

Abstract: The Sistan Basin has been recognized as one of the most active dust sources and windiest desert environments in the world. Although the dust activity in Sistan maximizes during the summer, rare but intense dust storms may also occur in the winter. This study aims to elucidate the atmospheric dynamics related to dust emission and transport, dust-plume characteristics, and impacts on aerosol properties and air quality during an intense dust storm over Sistan in February 2019. The dust storm was initiated by stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…The secondary peak seen in February (mid-winter) is associated with dust storms generated over the Arbaian Peninsula by southward propagating baroclinic systems from the mid-latitudes (e.g. Abdi Vishkaee et al, 2012;Kaskaoutis et al, 2019;Notaro et al, 2013). As highlighted in Yu et al (2016), even though the winter Shamal is stronger than its summer counterpart, with near-surface wind speeds in the Arabian Gulf of up to 20 m s -1 , the summer Shamal occurs more frequently, and is closely related to dust concentrations in the Gulf region.…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The secondary peak seen in February (mid-winter) is associated with dust storms generated over the Arbaian Peninsula by southward propagating baroclinic systems from the mid-latitudes (e.g. Abdi Vishkaee et al, 2012;Kaskaoutis et al, 2019;Notaro et al, 2013). As highlighted in Yu et al (2016), even though the winter Shamal is stronger than its summer counterpart, with near-surface wind speeds in the Arabian Gulf of up to 20 m s -1 , the summer Shamal occurs more frequently, and is closely related to dust concentrations in the Gulf region.…”
Section: Accepted Articlementioning
confidence: 99%
“…The peak in aerosol loading is in the summer, more precisely in July‐August (Figure 8), when the extinction coefficient exceeds 0.2 km −1 in the lowest 2–3 km of the atmosphere. The secondary peak seen in February (mid‐winter) is associated with dust storms generated over the Arabian Peninsula by southward propagating baroclinic systems from the mid‐latitudes (Abdi Vishkaee et al., 2012; Kaskaoutis et al., 2019; Notaro et al., 2013). As highlighted in Yu et al.…”
Section: Annual Diurnal Seasonal and Interannual Variability Of Aodmentioning
confidence: 99%
“…Poor visibility and sand encroachment, as a result of SDS, increase incidence of road accidents and aviation hazards, and disrupt supply chain infrastructures, communication, and transportation [25]. Overall, the SDSs affect the whole climate system and can cause changes in the earth's radiation balance and drought intensification [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the dust activity can be higher during summer due to 1) increased gustiness arising from the development of local convection and resulting cold pools (e.g., Bou Karam et al, 2014;Francis et al, 2019); 2) northward propagation of the ITD and associated near-surface turbulent mixing (Bou Karam et al, 2008; 3) development of dry cyclones from cut-off lows over the Arabian Peninsula (Francis et al, 2019) and strong convergence along the ITD (Francis et al, 2020). The secondary peak in February, associated with the intrusion of cold fronts from mid-latitudes (Kaskaoutis et al, 2019) reported by Nelli et al (2021b), is not seen at the location of Barakah. Instead, there is a steady increase in AOD throughout the winter season at a rate of roughly 0.2 months −1 consistent with the strengthening of the winds (Figures 4A,B), and the gradual drying of the surface.…”
Section: Aerosol Statisticsmentioning
confidence: 76%